Arranjo espacial, densidade e época de semeadura no acúmulo de matéria seca e nutrientes de três adubos verdes - Lima, Juliana Domingues [UNESP]; Sakai, Ronaldo Kazuo; Aldrighi, Michel; Sakai, Mauro (Escola de Agronomia e Engenharia de Alimentos/UFG, 2010)
The main objective of the study was to evaluate the effect of sowing densities, spatial arrangements and sowing dates in the accumulation of dry matter and nutrients in Crotalaria juncea, Mucuna deeringiana, and Cajanus cajan, in Pariquera-Açu, Vale do Ribeira, São Paulo State, Brazil. Three experiments were carried out: 1) sowing density x green manures, 2) spatial arrangement x green manures, and 3) sowing date x green manures. The experimental design was randomized complete blocks, with four replications, with the first experiments in a factorial scheme and the third in a split-plot arrangement. When plants reached 50% of flowering, the accumulation of dry matter, macronutrients, micronutrients, and organic carbon in the shoot were determined. Higher sowing densities reduce the accumulation of dry matter, B, and Zn, in Crotalaria juncea and Mucuna deeringiana; the accumulation of P in Mucuna deeringiana and Cajanus cajan; and the accumulation of N, S, and Cu in all green manures. The spatial arrangement does not affect the accumulation of dry matter and nutrients. Based on the accumulation of dry matter and nutrients, Crotalaria juncea is the most efficient species for use as green manure, when sown in November. Crotalaria juncea, Mucuna deeringiana, and Cajanus cajan show low performance in the accumulation of dry matter and nutrients, when sown at later dates.

Objetivou-se avaliar o efeito de densidades de semeadura, arranjos espaciais e épocas de semeadura no acúmulo de matéria seca e nutrientes de Crotalaria juncea, Mucuna deeringiana e Cajanus cajan, em Pariquera-Açu, Vale do Ribeira (SP). Três experimentos foram conduzidos: 1) densidade de semeadura x adubos verdes, 2) arranjo espacial x adubos verdes e 3) época de semeadura x adubos verdes. O delineamento experimental adotado foi o de blocos casualizados, com quatro repetições, sendo os primeiros experimentos arranjados em esquema fatorial e o terceiro em parcela subdividida. Quando as plantas atingiram 50% de floração, foram determinados o acúmulo de matéria seca, macronutrientes, micronutrientes e carbono orgânico na parte aérea. Maiores densidades de semeadura reduzem o acúmulo de matéria seca, B e Zn em Crotalaria juncea e Mucuna deeringiana; o acúmulo de P em Mucuna deeringiana e Cajanus cajan; e o acúmulo de N, S e Cu em todos os adubos verdes. O arranjo espacial não afeta o acúmulo de matéria seca e nutrientes. Com base no acúmulo de matéria seca e de nutrientes, Crotalaria juncea é a espécie mais eficiente para uso como adubo verde, quando semeada em novembro. Crotalaria juncea, Mucuna deeringiana e Cajanus cajan apresentam baixo desempenho na acumulação de matéria seca e nutrientes, quando semeadas em épocas tardias.
Spatial arrangement, sowing density and date on dry matter and nutrient accumulation of three green manures
Keywords: Crotalaria juncea; Mucuna deeringiana; Cajanus cajan; phytomass; Crotalaria juncea; Mucuna deeringiana; Cajanus cajan; fitomassa